Distribution of Different Scrippsiella acuminata (Dinophyta) Cyst Morphotypes in Surface Sediments of the Black Sea: A Basin Scale Approach - Dzhembekova, Nina; Rubino, Fernando; Belmonte, Manuela; Zlateva, Ivelina; Slabakova, Nataliya; Ivanova, Petya; Slabakova, Violeta; Nagai, Satoshi; Moncheva, Snejana (Frontiers in Marine Science, 2022)
Plankton cyst abundance and distribution is controlled by multiple factors. The stress linked to the fluctuations and variations of the environmental conditions in the water column is a major vector of encystment and intraspecific variability is an important adaptive strategy. The present study aims to disclose a link between the spatial distribution and abundance of different cyst morphotypes of Scrippsiella acuminata complex in surface sediments collected in the Black Sea at 34 sites and selected environmental variables. With this purpose, a basin scale data set was analyzed for patterns of intraspecific spatial heterogeneity. Redundancy analysis (RDA) was implemented to identify explanatory environmental variables associated with the cyst morphotypes abundance. Environmental multiyear data were used to ensure better approximation of a model that links environmental gradients with cyst abundance. Our results show that all S. acuminata cysts morphotypes are significantly correlated to one or a combination of the environmental variables, i.e., salinity, temperature and nutrients (nitrates and phosphates). The geographical distribution of Scrippsiella blooms in the Black Sea indicates that the interplay between the planktonic and benthic habitat of the dinoflagellate gives to S. acuminata the advantage to dominate in the plankton communities.